The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21303/2504-5679.2021.001856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding of chelated zinc form on security, productivity and slaughter parameters of broilers

Abstract: The results of the effect of feeding the chelated form of Zinc on the safety, productivity and slaughter parameters of broiler chickens are presented. The aim of this study was to determine the safety, productivity and slaughter parameters of broilers on the background of feeding chelated form of Zinc. Materials and methods. Experimental studies were conducted during 2020 on broiler chickens cross Cobb-500 in the vivarium of the Veterinary Faculty of Sumy National Agrarian University (Ukraine), div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The live weight of broiler chickens on day 8 in all three groups was almost the same at 230.2-239.5 g. Over the next week, after the introduction of the additives under study into the diet, the poultry began to grow more intensively and in the second group the live weight of chickens was 97% higher (at p<0.001), in the third group -by 10.5%. The absolute increase in live weight during the period of feeding the starter feed (days [3][4][5][6][7][8][9][10][11][12][13][14][15] was 11.7% higher in the second group (p<0.01), and 12.7% higher in the third group (p<0.001) compared to the data in the control group. The relative increase in live weight, which characterises the growth rate, during this period of poultry rearing with the introduction of the additive "Kronocid-L" to the diet is 3.3 p.p.…”
Section: Resultsmentioning
confidence: 99%
“…The live weight of broiler chickens on day 8 in all three groups was almost the same at 230.2-239.5 g. Over the next week, after the introduction of the additives under study into the diet, the poultry began to grow more intensively and in the second group the live weight of chickens was 97% higher (at p<0.001), in the third group -by 10.5%. The absolute increase in live weight during the period of feeding the starter feed (days [3][4][5][6][7][8][9][10][11][12][13][14][15] was 11.7% higher in the second group (p<0.01), and 12.7% higher in the third group (p<0.001) compared to the data in the control group. The relative increase in live weight, which characterises the growth rate, during this period of poultry rearing with the introduction of the additive "Kronocid-L" to the diet is 3.3 p.p.…”
Section: Resultsmentioning
confidence: 99%
“…Considering its dominant degree of oxidation, Zinc (Zn) (Gomathi et al, 2018) is an integral part of several biochemical pathways as a catalytic or regulatory co-factor. It also has a structural role in many other functional proteins (Fotina et al, 2021). (Mn) plays an essential role in various biological processes, being a significant co-factor of superoxide dismutase, transferase, hydrolase, and lyase (Bai et al, 2014;Xiao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In research, scientists have found that the use of chelated compounds of Zinc, Copper, and Manganese, as a feed additive, stimulates an increase in the overall natural resistance of broilers, accompanied by an increase of 7.4 % bactericidal activity, 8.3 % phagocytic activity, and 6,6 % of lysozyme activity. In this regard, chelated elements should be used in industrial poultry, as they can be used as a potent immunostimulant that provides good quality products without antibiotics (Fotina et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is found in several metalloenzymes such as RNA polymerase, carbonic anhydrase, and several others that affect nutrient metabolism. Zinc absorption mainly occurs in the small intestine [6]. The Zn requirement for a growing heifer is 200-300 mg and 22.8 mg/kg of ration.…”
Section: Introductionmentioning
confidence: 99%